Robotic Adrenalectomy: An Initial Experience in a Turkish Regional Hospital - Erdemir, Ayhan; Rasa, Kemal (Frontiers in Surgery, 2022)
Background: Due to the technical advantages and the convenience it provides to surgeons, "robotic adrenalectomy" is a widely used procedure for adrenal surgeries. In this study we aim to evaluate our robotic adrenalectomy experience and delineate the factors that have a susbtantial impact on surgical outcomes. Methods: Successive thirty transperitoneal robotic operations using daVinci SI® platform were grouped according to the surgery side, malignant or benign pathologies, for adenoma or non-adenoma lesions, tumor size of less than 4 cm or above, body mass index below or above 30 kg/m2 and with or without laparotomy history. Groups were compared in terms of duration of the operations, amount of bleeding, and the duration of hospitalization. Results: Morbidity developed in 5 patients (16.6%) and no mortality was observed. We had only one conversion to perform open surgery (3.3%). Operations performed for adenoma significantly last longer when compared with non-adenoma group (p<0.05). In the malignant group the amount of bleeding during surgery was found to be significantly higher (p<0.05). The blood loss during the surgery was also found to be higher in adenoma group when compared with the non-adenoma match (p<0.05). Phenomenally operative blood loss was found to be less at the bigger tumor size group (> 4 cm) when compared with the smaller size (p<0.05). Conclusion: Our results corroborate that robotic adrenalectomy may be more challenging for malignant pathologies and adenomas but can claim that it is an effective and safe option for all adrenal gland pathologies.